COGNITIVE LEARNING STYLES THE IMPACT OF FLIPPED CLASSROOM ON READING COMPREHENSION OF HIGH SCHOOL STUDENTS WITH DIFFERENT - Winda Syafitri (Journal MELT (Medium for English Language Teaching), 2016)
This study was intended to investigate the impact of flipped classroom on reading comprehension of high school students with different cognitive learning styles. This research was quasi-experimental with a factorial design 2x2 using pre-test and post-test. The population of study was the tenth graders of SMA Negeri 1 Malang. Then, X MIA-8 and X MIA-3 were chosen as samples by using simple random sampling. In collecting the data, reading comprehension test, questionnaire of students’ cognitive learning styles, opinionnaire and observation sheets were used as the instruments. After analyzing the data, the major findings are that there is no significant difference between students’ reading comprehension taught in the flipped classroom and those taught in the traditional classroom, that field-independent students have better reading comprehension than field-dependent students, an